Path Coefficient Analysis and Selection Index in Different Rice (Oryza sativa L.) Genotypes - Saddam Hussein Abbas (Kufa Journal for Agricultural Sciences)
Improving the grain yield in rice can be done more efficiently by selecting the yield components than selecting the grain yield itself, provided that these traits have a desirable genetic correlation with the grain yield trait. A field experiment was carried out in the rice research station in Al-Mashkhab/ Najaf/ IRAQ to determine the traits correlated with grain yield and to select the superior genotypes with their selection index among the sixteen genotypes planted during the growing season of 2021. During the 2022 season six genotypes were selected to evaluate the path coefficient analysis for the grain yield and its components according to randomized complete block design (RCBD) with three replicates. The results showed that the mean squares of the genotypes were significant for all studied traits(P<0.1). The superiority of the genotypes Furat1, Jasmine and K2 over the rest of six genotypes that were selected for having a high selection index, especially in the trait of grain yield, number of tillers.m-2 and number of grains.panicle-1. The genetic and phenotypic path coefficient analysis revealed that there was a high direct effect of the yield components on the grain yield due to the high positive and desirable values of the genetic and phenotypic correlation between the grain yield and its components including the number of tillers.m-2, the number of grains.panicle-1 and the panicle length, which are selective indicators for improving grain yield. Furthermore, the aforementioned traits showed high values of heritability in the broad sense and good stability during the two study seasons. Thus, the characteristics of the number of tillers.m-2 and the number of grains per panicle can be considered as one of the best criteria to be adopted as a selection index in the breeding programs for the rice crop. Moreover, further investigations are required for these criteria at different experimental conditions in other to testing their efficiency.